E-cigarette vapor amplifies neutrophilic inflammation and proteolytic EVs in response to LPS - Rasmussen, Lawrence W.; Finley, Dakota C.; Smith, Julian B.; Noa, Aaron S.; Blalock, J. Edwin; Gaggar, Amit; Madison, Matthew C. (Frontiers in Immunology, 2025)
BackgroundWhile e-cigarette use (vaping) has increased in the last decade, its effects on airway inflammation and extracellular vesicle (EV) biology remain unclear. This study examined how long-term and acute vapor exposures influence lung immune responses, neutrophilic inflammation, and EV-associated proteolytic activity.MethodsMice were exposed daily to vapor from commercial e-cigarettes or room air for up to 12 weeks. After exposure, we assessed immune cell recruitment, alveolar damage, and EV populations in the airways. To explore vapor-mediated effects on secondary lung injury, a lipopolysaccharide (LPS) challenge was administered after two weeks of vapor exposure. We then analyzed immune cell responses and isolated neutrophil-derived EVs (nEVs) for transfer into naïve mice to evaluate pathogenic potential.ResultsVapor exposure alone did not significantly alter immune cell infiltration, lung histology, or EV protease activity. However, mice pre-exposed to vapor and then challenged with LPS showed increased neutrophil infiltration, elevated neutrophil elastase activity in EVs, and greater alveolar damage. Furthermore, nEVs from these mice induced more severe emphysematous changes when transferred to unexposed mice.ConclusionsWhile e-cigarette vapor alone does not provoke marked airway inflammation or proteolytic EV release, it creates a primed immune state. This priming amplifies inflammatory and destructive responses to subsequent challenges. These findings suggest vaping may exacerbate lung damage when combined with infections or other environmental stressors, raising concerns about its role in worsening pulmonary disease.